Development of a dual-acting axial piston pump for displacement-controlled system. (April 2014) - Huang, Jiahai; Quan, Long; Zhang, Xiaogang
Pump-controlled hydraulic systems can effectively eliminate throttling losses, but one issue is the unequal flow rate through an asymmetric actuator, which is widely used in hydraulic systems. In this study, a new concept of asymmetric pump is presented, which is a kind of swash plate axial piston pump, with four ports, that intakes and discharges oil twice in one revolution cycle. According to the area ratio of a single-rod cylinder, λ, flow rate ratio of its two delivery ports was designed as (1 − λ ): λ, and then a basic equation about the distribution method of the asymmetric pump was obtained. Based on that, a fixed displacement dual-acting axial piston pump was designed and manufactured. Simulation and experimental results show that the operation principle of the displacement dual-acting axial piston pump is feasible. Finally, qualitative tests of displacement dual-acting axial piston pump–controlled system were carried out in the laboratory. The test results reveal that displacement dual-acting axial piston pump can be used in a closed-circuit hydraulic system, demonstrating that the analysis of this study might be a groundwork for a new exploration in displacement-controlled systems.